Understanding the phenomenological experiences of schema therapy for those with an eating disorder - Alice Cunningham; Marie Reid; Stephanie Sayan; Richard Hammersley (Qualitative Research in Medicine & Healthcare, 2024)
Schema therapy expands traditional cognitive-behavioral models, weakening early maladaptive schemas and schema modes while strengthening adaptive modes. This study investigated participant experiences of schema therapy for eating disorders, focusing on schema modes and the eating disorder voice, how these maintained disordered eating, and how therapy helped. Semistructured online video interviews with clients receiving schema therapy for eating disorders (N=10) were analyzed using interpretative phenomenological analysis. Four group experiential themes were developed: (1) adverse experiences, typically in childhood and adolescence, (2) interpersonal relationships, especially with primary caregivers and the benefits of a good therapeutic relationship, (3) self-awareness of schema modes and the eating disorder voice and their impact on participants’ eating disorders, and (4) recovery using schema concepts, including finding one’s inner child, better self-management, and ambivalence about recovering. Overall, schema therapy was perceived as beneficial, specifically regarding participants’ awareness of their inner child, development of their eating disorder, and awareness of their eating disorder voice. Participants expressed a growing positive sense of agency, connecting with their inner child’s needs and developing a connection to their healthy adult mode. They also felt that schema therapy had equipped them with the tools to strengthen their healthy adult mode, while simultaneously weakening their maladaptive modes.